# math

posted by .

lim (7-6x^5)/(x+3)....
the lim is x->+infinity
[ans=-infinity but i get 0]
can someone show me the calculation work.

• math -

dividing the expression results in a leading term of
-6x^4
as x --> + infinity
-6x^4 ---> - infinity

## Similar Questions

1. ### calculus - interval of convergence

infinity of the summation n=0: ((n+2)/(10^n))*((x-5)^n) .. my work so far. i used the ratio test = lim (n-->infinity) | [((n+3)/(10^(n+1)))*((x-5)^(n+1))] / [((n+2)/(10^n))*((x-5)^n)] | .. now my question is: was it ok for me to …
2. ### calculus - interval of convergence

infinity of the summation n=0: ((n+2)/(10^n))*((x-5)^n) .. my work so far. i used the ratio test = lim (n-->infinity) | [((n+3)/(10^(n+1)))*((x-5)^(n+1))] / [((n+2)/(10^n))*((x-5)^n)] | .. now my question is: was it ok for me to …
3. ### Calc. Limits

Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- infinity so lim x->0+ = + infinity?
4. ### calc

Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- infinity so lim x->0+ = + infinity?

Are these correct? lim x->0 (x)/(sqrt(x^2+4) - 2) I get 4/0= +/- infinity so lim x->0+ = + infinity?
6. ### Calculus

Find the horizontal asymptote of f(x)=e^x - x lim x->infinity (e^x)-x= infinity when it's going towards infinity, shouldn't it equal to negative infinity, since 0-infinity = - infinity lim x-> -infinity (e^x)-x= infinity
7. ### math

i really don't understand why this 1-lim 3/(y+4) [the lim is x->infinity] the ans is 0 while this 2-lim (7-6x^5)/(x+3) [x->+infinity ] is - infinity. can anyone explain why the 1 is zero & the 2 is infinity.
8. ### math

solve lim (5000t^2)/ (t+2)^2. the lim is t->infinity. can someone show me the calculation. the ans is 5000.
9. ### Math

1. If -1/infinity = infinity or -infinity ?
10. ### Math

1. If -1/infinity = infinity or -infinity ?

More Similar Questions